2015
DOI: 10.1002/ddr.21254
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kramecyne on LPS Induced Chronic Inflammation and Gastric Ulcers

Abstract: Preclinical Research Krameria cytisoides is used for the treatment of inflammation, stomach pain, and gastric ulcers. The active ingredient from this plant is a peroxide, kramecyne (KACY) which has anti-inflammatory effects. The aim of the present study was to evaluate the anti-inflammatory activities of KACY in lipopolysaccharide (LPS)-induced systemic chronic inflammation in mice for 60 days, using dexamethasone (DEX) as the positive control, vehicle (the LPS group) as the negative control and the control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…It is composed of six monomers of epoxide with the formula C 30 H 8 O 4 (Pérez et al, 2012). This compound has not only demonstrated activity similar to Krameria cytisoides Cav , but also produced other beneficial effects according to pharmacological studies on animals (Sánchez et al, 2013, Alonso et al, 2015a, Alonso et al, 2015b). An in vivo experiment reported that at a dose of 250 μg/mL in a culture of macrophages, this polymer induced a low level of toxicity, evidenced by an LD 50 greater than 5000 mg/kg (Pérez et al, 2012), and a low level of cytotoxicity (Sánchez et al, 2013).…”
Section: Introductionmentioning
confidence: 95%
“…It is composed of six monomers of epoxide with the formula C 30 H 8 O 4 (Pérez et al, 2012). This compound has not only demonstrated activity similar to Krameria cytisoides Cav , but also produced other beneficial effects according to pharmacological studies on animals (Sánchez et al, 2013, Alonso et al, 2015a, Alonso et al, 2015b). An in vivo experiment reported that at a dose of 250 μg/mL in a culture of macrophages, this polymer induced a low level of toxicity, evidenced by an LD 50 greater than 5000 mg/kg (Pérez et al, 2012), and a low level of cytotoxicity (Sánchez et al, 2013).…”
Section: Introductionmentioning
confidence: 95%